Benzoylcholine, Indole-3-acetic And Human Serum Butyrylcholinesterase Interactions - Ebru Bodur; A. Neşe Çokuğraş (Türk Biyokimya Dergisi, 2006)
In this study we studied the kinetic interaction of indole-3- acetic acid with human serum butyrylcholinesterase. Butyrylcholinesterase was purified from human serum and the benzoylcholine kinetics was analyzed. The enzyme had a Km value of 14.22 ± 2.97 μM. The Hill plot was linear with a value of nH = 0.95, displaying that the enzyme follows Michaelis-Menten kinetics with regard to benzoylcholine. Through inhibition studies, indole-3-acetic acid was found to be a noncompetitive inhibitor for human serum butyrylcholinesterase with benzoylcholineas substrate. The Ki value was calculated as 1.86 ± 0.27 mM. In our previous study on human serum butyrylcholinesterase using butyrylthiocholine as substrate, indole-3-acetic acid was found to be a linear-mixed type inhibitor.This difference in kinetic behavior with regards to two different substrates could arise from the tighter binding of the more bulky and hydrophobic benzoyl group to the hydrophobic pocket of the active site gorge rather than the butyryl group and that the binding of this butyryl group could be sterically hindered by the indole-3-acetic acid.